PEMENUHAN HAK-HAK PT. JAMKRIDA RIAU SEBAGAI PENJAMIN DALAM PENYELESAIAN KREDIT USAHA RAKYAT DENGAN CARA SUBROGASI - Afni Syafitri; Hayatul Ismi; Riska Fitriani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
Subrogation is one way of salvaging credit, where subrogation is a third party who has paid the debtor's debt by law appearing as a new creditor who replaces the position of the old creditor or the old debtor against the debtor who owes it. The subrogation carried out by the third party here is not to free the debtor from his debts and obligations, but to replace the old creditor to become a new creditor so that the debtor has an obligation to pay his debt to the third party as a new creditor.This study aims to see the fulfillment of the rights of PT. Jamkrida Riau by Bank Riau Kepri as guarantor in the settlement of People's Business Credit by means of subrogation. Furthermore, Bank Riau Kepri be careful in fulfilling the rights of PT. Jamkrida Riau by Bank Riau Kepri as guarantor in the settlement of People's Business Credit by means of subrogation.The type of research used is sociological legal research with interview techniques. The research found that the rights of PT. Jamkrida Riau that is not fulfilled is the repayment of collateral for claims that have been paid to Bank Riau Kepri. PT. Jamkrida Riau has obtained the Guarantee Fee (IJP) from the debtor at the beginning of the loan loan. The efforts of Bank Riau Kepri in fulfilling the rights of PT. Jamkrida Riau is carrying out credit restructuring of the guarantor who has good faith and is responsible. Performing credit execution, the proceeds of the collateral disbursement are dividedJOM Fakultas Hukum Universitas Riau Volume VII No. 2 Juli – Desember 2020 Page 2proportionally. The results of the disbursement of credit collateral that are obtained exceeds the guaranteed debt, then it is returned to the guaranteed.Keyword: Subrogation, fulfillment of rights, Credit Settlement